Generalized Peukert Equation with Due Account of Temperature for Estimating the Remaining Capacity of Nickel–Metal Hydride Batteries - Nataliya N. Yazvinskaya (Inorganics, 2022)
In this paper, it is experimentally proven that the generalized Peukert equation C(i,T) = Cm(T)/(1 + (i/i0(T))n(T)) is applicable to nickel–metal hydride batteries at any discharge currents, while the classical Peukert equation can be used only in a limited range of the discharge currents (approximately from 0.3 Cn to 3 Cn). In addition, the classical Peikert equation does not take into account the influence of the temperature of a battery on its released capacity. It is also proven that for the nickel–metal hydride batteries, the generalized Peukert equation heavily depends on battery temperature (via the parameters Cm(T), i0(T) and n(T)). The temperature dependencies of the parameters of the generalized Peukert equation and their physical meaning are also established. The obtained generalized Peukert equation, which considers the batteries’ temperature, can be used at any discharge current and temperature of the batteries.